STRATEGI PENGEMBANGAN USAHATANI BAWANG PUTIH DI KECAMATAN CIWIDEY KABUPATEN BANDUNG - Syam Ahmad Sopian; Luciana Trimo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Garlic production in Indonesia can be judged to be unstable and far below market needs. Garlic production in 2017 in Indonesia is 19,510 tons. The production yield decreased from total garlic production in 2016 which reached 21,150 tons. The amount of garlic production is still unable to meet the needs of the Indonesian people who reach 500,000 tons / year (Kementan, 2017). Meanwhile, the need for consumption of garlic in Indonesia from year to year continues to increase in line with the increasing population. However, this increase has not been able to offset the increase in domestic production. For this reason, it is necessary to study a prospect of developing garlic at a central location, one of which is in Ciwidey District, Bandung Regency. This research aim to 1) describe of garlic farming from technical, economic, and social aspects 2) design alternative development strategy for garlic. The research location in Ciwidey District Bandung Regency is purposefully choosen because it is highland vegetable central and ever become garlic producent. The result shows that environmental condition in Ciwidey suits the requirements for garlic to grow, garlic farming in Ciwidey District is still worthy to be endevored economically because of the R/C value that is 1,24 which means still can be benefitting. On the other hand, farmer perception can be categorized positive which means they have the hope to developt to developt garlic farming. The recommended strategy is agressive strategy because garlic farming in Ciwidey District appears to be very benefitting because of the power to maximize the existing opportunies. Therefore, the right strategy and should be preferred in the attempt to developt garlic farming in Ciwidey District is to increase the production of garlic in integrated way with expanding the planning areal, empowering farmer groups, and growing seed breeder to provide the needs of high quality garlic seeds.